The interrelation between Baltic Dry Index a practical economic indicator and emerging stock market indices. (24th April 2019) - Manoharan, M.; Visalakshmi, S.
The Baltic Dry Index is a leading indicator that generates a vibrant panorama on the global demand for commodities and raw materials as it provides a glimpse into the future. This study uses the analytical content of the Baltic Dry Index (BDI) to explore the relationship between maritime markets and stock markets with respect to emerging markets and the Stock Indices of India and China (i.e., NIFTY and Shanghai Composite Index) using VAR SURE modelling, impulse response and VAR Granger causality test for the period 1st January 2011 to 31st December 2015. The overall results exhibit that BDI influences NIFTY marginally and also produces a slight impact on SSE composite index due to the influence of international economic environment, particularly by international traders. The resulting model will aid investors and decision makers to make their financial conclusions more precisely.